Intellectual property considerations for molecular diagnostic development with emphasis on companion diagnostics. (1st February 2018) - Glorikian, Harry; Warburg, Richard Jeremy; Moore, Kelly; Malinowski, Jennifer
ABSTRACT: Introduction : The development of molecular diagnostics is a complex endeavor, with multiple regulatory pathways to consider and numerous approaches to development and commercialization. Companion diagnostics, devices which are "essential for the safe and effective use of a corresponding drug or diagnostic product" (see U.S. Food & Drug Administration, In Vitro Diagnostics - Companion Diagnostics, U.S. Dept. of Health & Human Services(2016), available at https://www.fda.gov/medicaldevices/productsandmedicalprocedures/invitrodiagnostics/ucm407297.htm ) and complementary diagnostics, which are more broadly associated with a class of drug, are becoming increasingly important as integral components of the implementation of precision medicine. Areas covered : The following article will highlight the intellectual property ('IP') considerations pertinent to molecular diagnostics development with special emphasis on companion diagnostics. Expert opinion/commentary Summary : For all molecular diagnostics, intellectual property (IP) concerns are of paramount concern, whether the device will be marketed only in the United States or abroad. Taking steps to protect IP at each stage of product development is critical to optimize profitability of a diagnostic product. Also the legal framework around IP protection of diagnostic technologies has been changing over the previous few years and can be expected to continue to change in the foreseeable near future, thus, a comprehensive IP strategy should take into account the fact that changes in the law can be expected.